Multiple Chronic Conditions - Monica A. Fisher PhD, DDS, MS, MPH; Zhen-qiang Ma MD, MPH, MS (SAGE Publishing, 2014)
Background: Multiple chronic conditions (MCCs) are significant public health problems receiving much attention, and rightly so, because of the substantial morbidity, mortality, and cost burden. Objectives: To report the prevalence of selected frequent MCCs with shared risk factors that are leading causes of death; and to quantify the association between diabetes and its comorbidity and shared risk factors. Methods: This is a cross-sectional study of 9172 participants in Pennsylvania's 2009 Behavioral Risk Factor Surveillance System (BRFSS). Centers for Disease Control and Prevention's Web Enabled Analysis Tool (WEAT) and SAS Proc Survey were used for all analyses, to account for BRFSS's multistage complex survey design and sample weights. Results: SAS estimated prevalence among ≥35-year-olds were as follows: diabetes (11.9%), heart disease (9.5%), stroke (3.3%), diabetes and heart disease (2.9%), diabetes and stroke (1.0%), heart disease and stroke (1.1%), and diabetes, heart disease, and stroke (0.4%). Adults ≥35 years old with the following characteristics were more likely to have diabetes when self-reporting: obese (adjusted odds ratio [OR Adj ] = 4.63, 95% confidence interval [95% CI] = 3.41-6.30); low income (<$15 000 OR Adj = 2.85, 95% CI = 1.90-4.27; $15 000-$24 999 OR Adj = 2.07, 95% CI = 1.50-2.86; $25 000-$34 999 OR Adj = 2.06, 95% CI = 1.47-2.88; $35 000-$49 999 OR Adj = 1.51, 95% CI = 1.08-2.12); elderly ≥65 years old (OR Adj = 2.84, 95% CI = 1.76-4.56); non-Hispanic black (OR Adj = 2.54, 95% CI = 1.08-6.00); overweight (OR Adj = 1.99, 95% CI = 1.47-2.68); heart disease (OR Adj = 1.94, 95% CI = 1.47-2.56); 45 to 64 years old (OR Adj = 1.88 95%, CI = 1.21-2.93); hypertension (OR Adj = 1.78, 95% CI = 1.39-2.29); stroke (OR Adj = 1.62, 95% CI = 1.05-2.50); high cholesterol (OR Adj = 1.49, 95% CI = 1.18-1.88); physically inactive (OR Adj = 1.33 95% CI = 1.06-1.67); and men (OR Adj = 1.32, 95% CI = 1.04-1.67). Conclusion: Adults with comorbidity and risk factors were 1.3 to 4.6 times more likely to have diabetes, with obesity consistently the strongest risk factor. WEAT's limitations are the predefined categories, inability to restrict to specific age groups and to estimate the prevalence of >2 MCCs. WEAT has considerable potential to advance evidence-based primary care practice and community health programs, such as state-wide programs that target obesity and physical inactivity. The robust capability of SAS to calculate MCC prevalence and adjusted associations with risk factors provides the fundamentals for developing and evaluating primary care services and community health programs.